The Writer's handbook. - Olsen, Udia G.; Werby, Elaine P.; Houghton, Samuel G. (Samuel Gilbert) 1902-1975; Burack, A. S. (Abraham Saul) 1908-
"Manuscript market section", ed. by U. G. Olsen, 1941-44; by E. P. Werby, 1945-